Redescription of the Indo-Pacific scorpionfish Scorpaenodes guamensis (Quoy & Gaimard 1824) (Scorpaenidae), a senior synonym of seven nominal species - Motomura, Hiroyuki; Causse, Romain; Struthers, Carl D. (Zootaxa, 2016)
The Indo-Pacific scorpionfish, Scorpaenodes guamensis (Quoy & Gaimard 1824), is redescribed on the basis of 137 specimens, including types, from a wide geographic range in the Indo-Pacific. Seven nominal species, Scorpaena rubropunctata Cuvier in Cuvier & Valenciennes 1829, Sebastes minutus Cuvier in Cuvier & Valenciennes 1829, Scorpaena chilioprista Rüppell 1838, Scorpaena polylepis Bleeker 1851, Centropogon echinatus Macleay 1881, Scorpaena erinacea Garman 1903, and Scorpaenopsis quiescens Seale 1906, are regarded here as junior synonyms of S. guamensis. The type status of these nominal species is discussed, and lectotypes of Scorpaena guamensis, Scorpaena rubropunctata, Sebastes minutus, and Scorpaena polylepis are herein designated. Validity of Scorpaenopsis scaber (Ramsay & Ogilby 1886) is also discussed.